Optimizing Sharia Bank Digitalization Efforts to Improve the National Economy and Human Resources in the Industrial Era 4.0 - Andiansyah, Farma; Rini, Endang Sulistya; Absah, Yeni (ITB AAS INDONESIA Surakarta, 2024)
The movement of the community's economic structure experienced a very drastic decline in line with the spread of the COVID-19 virus. The Covid-19 pandemic has become a driving force for digitalization in almost all sectors, including payment systems. Digitalization of the payment system is considered to be the key to accelerating national economic recovery in addition to the COVID-19 vaccination program. This research aims to find out how the Digitalization of Sharia Banks Promotes National Economic Recovery during the COVID-19 pandemic. The research method used by the author in preparing this article is a literature review or literature study that contains theories that are relevant to the research problems. Several digital services can be put forward to encourage the acceleration of increasing sharia financial inclusion in Indonesia such as digital payment systems, peer-to-peer lending, and branchless banking. Increasing Sharia financial inclusion itself is carried out because it has a direct impact on improving the welfare of people who use digital-based Sharia financial services and products. Digitalization of Sharia banking can be the key to encouraging national economic recovery. The convenience of digital transaction services facilitates bank transaction activities amidst the limited mobility of community activities. So it cannot be denied that the Sharia banking industry has experienced an increase through digital banking services even though it has been hit by a crisis due to the COVID-19 pandemic.